Hemodynamic effects of contrast media and its adverse effects in Western Rajasthan: an observational study - Ali, Akhtar; Rathore, Rajkumar; Chaturvedi, Kirti; Parvez, Amreesh (International Journal of Basic & Clinical Pharmacology, 2019)
Background: This study was aimed to investigate the hemodynamic effects of CT scan contrast media on pulse rate and blood pressure as well as identify the possible adverse drug reactions occurring after administration of contrast media. Methods: Information of patients such as age, sex, diagnosis, prescribed body part for CT scan, amount of contrast media and route of administration of contrast media were collected. Pulse and blood pressure were measured three times, before administration of iohexol or diatrizoate sodium; after 5 min and 1 hr administration of iohexol; after 1 hr and 2 hr starting of administration of diatrizoate sodium. ADR occurring after contrast media administration were observed. Results: Before Iohexol administration, SBP was 126.85±18.47 mmHg, which increased by 129.92±20.51 and 128.24±19.89 mmHg after 5 min. and 1 hr respectively after administration. Whereas before iohexol administration, DBP was 81.28±11.5 mm Hg, which was decreased by 80.58±13.03 and 78.90±13.15 mmHg after administration. The p-value for PR, pre-iohexol vs 1 hr post-iohexol was highly significant. Before Diatrizoate Sodium administration, SBP was 128.84±17.64 mmHg, that was decreased with 126.23±17.92 and 124.15±17.04 mmHg after administration. On the other hand, DBP was 81±11.99 mmHg which was decreased with 80.23±11.07 and 79.84±11.31 mmHg by Diatrizoate Sodium administration. P-value for SBP, DBP, and PR in various comparison of diatrizoate sodium administration was insignificant as well as total 18 ADRs were recorded post diatrizoate sodium and iohexol administration. Conclusions: Present study result demonstrates PR was significantly increased by administration of iohexol but not that much due to Diatrizoate Sodium especially after the 1 hr of iohexol administration. Although DBP decreased by both drugs, on the other hand, SBP increased by iohexol and decreased by Diatrizoate Sodium administration which was clinically insignificant. Although headache and giddiness were most common ADRs by both drugs.